2013
DOI: 10.1016/j.jmoldx.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and Clinical Validation of a Real-Time PCR Assay for PITX2 DNA Methylation to Predict Prostate-Specific Antigen Recurrence in Prostate Cancer Patients Following Radical Prostatectomy

Abstract: Prostate cancer is the most common cancer among men. The prospective discrimination of aggressive and clinically insignificant tumors still poses a significant and, as yet, unsolved problem. PITX2 DNA methylation is a strong prognostic biomarker in prostate cancer. Recently, a diagnostic microarray for prostate cancer prognosis based on PITX2 methylation has been developed and validated. Because this microarray requires nonstandard laboratory equipment, its use in a diagnostic setting is limited. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 29 publications
4
54
0
Order By: Relevance
“…In recent years, other variable DNA methylation alterations in neoplastic tissue samples have been also associated with the prediction of PSA recurrence after RP [10,17,18,19,20,21,22,23,24]. These studies have identified new potential tumor markers including methylation of PITX2 , HOXD3 , APC , TGFβ2 , RASSF1A , ANEP , PCDH10 , ZNF132 , TDRD1 , AOX1 , C1orf114 , GAS6 , HAPLN3 , KLF8 , MOB3B , CCND2 , PTGS2 , RARB , SRD5A2 and CYP11A1 , thus emerging as new predictors of BCR particularly in high-risk clinically localized disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, other variable DNA methylation alterations in neoplastic tissue samples have been also associated with the prediction of PSA recurrence after RP [10,17,18,19,20,21,22,23,24]. These studies have identified new potential tumor markers including methylation of PITX2 , HOXD3 , APC , TGFβ2 , RASSF1A , ANEP , PCDH10 , ZNF132 , TDRD1 , AOX1 , C1orf114 , GAS6 , HAPLN3 , KLF8 , MOB3B , CCND2 , PTGS2 , RARB , SRD5A2 and CYP11A1 , thus emerging as new predictors of BCR particularly in high-risk clinically localized disease.…”
Section: Discussionmentioning
confidence: 99%
“…The assays were sensitive down to 0.8% methylated DNA (equivalent to 40 pg) in a total of 5 ng bisulfite-converted DNA (Fig 2). The analytical performance of the PITX2ab-assay has been described in detail earlier [35]. …”
Section: Resultsmentioning
confidence: 99%
“…In spite of the presented possible biomarker capabilities, it becomes apparent that aberrant DNA methylation of PITX2 variants is not as prognostic for BTCs as it is for breast or prostate cancer [17,35]. In the latter, these markers may identify patients with an adverse clinical courses who might actually benefit from a radical treatment, while patients with a better prognosis might benefit from a more conservative treatment with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genes, including those that encode glutathione S-transferase π 1 (GSTP1), adenomatous polyposis coli (APC), Ras association domain-containing protein 1 (RASSF1A) and prostaglandinendoperoxide synthase 2 (PTGS2), have been demonstrated to be hypermethylated in PCa, but not in the normal prostate tissues (6,13,14). Similarly, many hypomethylated genes have been identified and demonstrated to be associated with the recurrent status of PCa patients (15)(16)(17). These findings suggest that the DNA methylation of these loci may improve the diagnostic efficiency for PCa.…”
Section: Introductionmentioning
confidence: 99%